2019
DOI: 10.1136/bmjopen-2018-028844
|View full text |Cite
|
Sign up to set email alerts
|

Doctor’s presenteeism and its relationship with anxiety and depression: a cross-sectional survey study in China

Abstract: ObjectivesThe impact of presenteeism on doctors’ health, quality of patient care and overall performance of health institutions has been reported. The study aimed to investigate the prevalence of presenteeism among doctors, the association between presenteeism and anxiety/depression, and aspects that can help alleviate presenteeism.DesignA cross-sectional anonymous survey study was conducted between 2017 and 2018.Setting30 hospitals in Hangzhou city, Zhejiang Province, China including 10 category 1 hospitals (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 46 publications
(50 reference statements)
0
16
1
Order By: Relevance
“…Our aim was to identify the determinative factors of the impact of COVID-19 on HCW's psychological status. A review of previous literature suggests that many factors can also affect the mental health of HCW in non-epidemic situations (19)(20)(21)(22). Further adjusted logistic regression showed that there was no significant correlation between the exposure risk and occupation, working years, and stigma and the psychological status of HCW during the outbreak of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our aim was to identify the determinative factors of the impact of COVID-19 on HCW's psychological status. A review of previous literature suggests that many factors can also affect the mental health of HCW in non-epidemic situations (19)(20)(21)(22). Further adjusted logistic regression showed that there was no significant correlation between the exposure risk and occupation, working years, and stigma and the psychological status of HCW during the outbreak of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that 23.9-68.8% of HCW suffered from mental health problems in China due to the high workload, promotion pressure, deteriorating doctor-patient relationships, medical disputes, and even violence (19)(20)(21)(22). On this basis, the outbreak of COVID-19 undoubtedly increased the psychological pressure of HCW, who were the soldiers in this battle.…”
Section: Discussionmentioning
confidence: 99%
“…However, most studies on presenteeism in the workplace have focused on European and Western countries (e.g., Britain, Sweden, the Netherlands, and the United States), and more empirical researches are still required to examine presenteeism behavior in an Eastern cultural context (Zhang and Li, 2016;Xi et al, 2019). Moreover, owing to the changing environment of economy and organizations, the increased work pressure and unemployment rate foster employees' job insecurity (Cheng and Chan, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In China, the prevalence of presenteeism among doctors was found to be consistently higher, ranging from 47.5% for primary medical staff 40 to 66.4% for hospital doctors 41 as compared to as low as 15% among other employees 42 . Hospital doctors are especially prone to presenteeism mainly due to high job demand and intense occupational stress.…”
Section: Introductionmentioning
confidence: 97%